**Pragmatic Analysis of Prophetic Discourse – The Hadiths of Social Interaction as a Model** - lemounes, khayreddine; Lagdi, Mohamed (El Omda in Linguistics and Discourse Analysis, 2022)
Researchers have been studying language since ancient times, and they have taken a variety of approaches to that. The importance of the pragmatic lesson in trying to understand linguistic usage, through the multiple contexts, the intentions of the speakers, and taking care of the discourse and its culprits. Therefore, this study seeks to try to apply the mechanisms of the pragmatic approach to the prophetic discourse, and trace the features of this approach and the extent of its openness to the linguistic achievement.